The EXCITE Stroke Trial: Comparing Early and Delayed Constraint-Induced Movement Therapy - Wolf, Steven L. (2010)
BACKGROUND AND PURPOSE: Although constraint-induced movement therapy (CIMT) has been shown to improve upper extremity function in stroke survivors at both early and late stages post-stroke, the comparison between participants within the same cohort but receiving the intervention at different time points has not been undertaken. Therefore, the purpose of this study was to compare functional improvements between stroke participants randomized to receive this intervention within 3–9 months (early group)to participants randomized upon recruitment to receive the identical intervention 15–21 months post-stroke(delayed group). METHODS: Two weeks of CIMT was delivered to participants immediately after randomization (early group) or one year later (delayed group). Evaluators blinded to group designation administered primary (Wolf Motor Function Test [WMFT], Motor Activity Log [MAL]) and secondary (Stroke Impact Scale [SIS]) outcome measures among the 106 early participants and 86 delayed participants prior to delivery of CIMT, two weeks thereafter and 4, 8 and 12 months later. RESULTS: While both groups showed significant improvements from pretreatment to 12 months post-treatment, the earlier CIMT group showed greater improvement than the delayed CIMT group in WMFT Performance Time and the MAL (P’s < .0001) as well as in Stroke Impact Scale Hand and Activities domains (P <. 0009 and .0214, respectively). Early and delayed group comparison of scores on these measures 24 months after enrollment, showed no statistically significant differences between groups. CONCLUSIONS: CIMT can be delivered to eligible patients 3 to 9 months or 15 to 21 months following stroke. Both patient groups achieved approximately the same level of significant arm motor function 24 months after enrollment. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00057018